Comment on "Spatial distribution of microplastic concentration around landfill sites and its potential risk on groundwater". (December 2021) - Lee, Jin-Yong; Cha, Jihye; Jeong, Eunju; Kim, Young-In
Abstract: This paper discusses some critical weak points and mistakes identified in the original paper. The authors disregarded the importance of field blanks, sampling equipment, and well specifications for proper quality assurance and control. Beneficial field practices guarantee highly reliable results of laboratory analysis for microplastics. In addition, polymer type (chemical composition) and shape (form) are different classification criteria, but the authors mixed these in their description. The distribution and transport of microplastics should be properly understood, along with a knowledge of groundwater flow conditions, such as flow direction and velocity, in the study area.